OCCUPATIONAL STRESS AND COPING STRATEGY HARMONY BETWEEN SCIENTIFIC THEORY AND ISLAMIC TEACHINGS AND PRACTICE - Ratri Atmoko Benedictus (MANASA, 2018)
As a country with the largest Moslem population, the workplace in Indonesia generally provides a place and time for the workers to perform their religious obligation, mainly for performing Sholat. The purpose of this literatures study was to probe several aspect of Islamic teaching and ritual from the scientific perspective which is  then able to be optimized its benefit for the work, in addition for religious intention, mainly in the management of occupational stress. Stress itself arises in the interaction between people and their environment, and coping strategy will determine how well they manage the stress. In summary, the result show that the types of stress according to the theory of Lasarus can be harmonized with the coping strategy based on Islamic teachings in Al Quran, especially in the Surah Al-Inshirah verses 1 through 8. Another important finding was that Sholat activity provides two physiological benefits, i.e. stimulates the relaxation of brainwaves and increase the muscle flexibility. Whereas, the suggestion to perform Sholat berjamaah or praying in group is in harmony with the collective culture of Indonesia, especially related to the value of silaturahmi or friendship and hospitality. Therefore, performing Sholat berjamaah during work is also able to strengthen the relationship between employees which might be utilized to express their emotion or even psychological burden. However, study in this  area still need to be improved to find other alignments that can optimize the role and benefits of religious activity in the workplace.